Eleventh IEEE European Test Symposium (ETS'06)
DOI: 10.1109/ets.2006.13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Voltage Scaling Aware Delay Fault Testing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that reducing the supply voltage increases the transistor channel resistance, which results in an increasing electrical impact of a gate-drain (or gatesource) resistive bridge defect, or a drain (or source) resistive open defect [10]. Circuit test under varying operating conditions has been studied in many works such as [24,25], which investigate the effect of supply voltage on the circuit delay and delay testing. The very-Low-Voltage test is exploited to detect ELF-related defects in [7,8].…”
Section: State Of the Artmentioning
confidence: 99%
“…It has been shown that reducing the supply voltage increases the transistor channel resistance, which results in an increasing electrical impact of a gate-drain (or gatesource) resistive bridge defect, or a drain (or source) resistive open defect [10]. Circuit test under varying operating conditions has been studied in many works such as [24,25], which investigate the effect of supply voltage on the circuit delay and delay testing. The very-Low-Voltage test is exploited to detect ELF-related defects in [7,8].…”
Section: State Of the Artmentioning
confidence: 99%